Potensi Ekstrak Enzim Daun Pepaya (Carica papaya L.) Sebagai Agen Fibrinolitik Dengan Metode Clot Lysis in Vitro - Hervina Warninghiyun; Ana Indrayati; Pudiastuti RSP (Journal Syifa Sciences and Clinical Research, 2023)
Stroke is a disease caused due to blockage of blood vessels. Health department in 2013 stated that 15,4% of people died from strokes. One of the treatment therapies that can be used is fibrinolytic. Fibrinolytic agents have a role in lysing blood clots, these agents can be obtained from microbes, plants and animals. This study aims to determine the protein content contained in papaya leaf enzyme extract (Carica papaya L.), and to determine the potential of the enzyme extract at certain concentrations as an alternative to natural fibrinolytic drugs. The study began with plant determination, sampling, enzyme extraction using a blender, purification of the extract by precipitation using ammonium sulphate, protein content determination using the Lowry method, and testing the fibrinolytic activity of the clot lysis method in vitro. Three series of test concentrations were made, namely 20, 40, and 80%. The results of the research on papaya leaf extract showed that the protein content in purification pellet 1 was 196,22 Âµg/ml and purification pellet 2 was 306,33 Âµg/ml. In papaya leaves, fibrinolytic activity was proven with the optimal percentage of blood clot lysis in purification pellet 2 with a concentration of 80% which was 79%.